Paroxysmal nocturnal haemoglobinuria testing in blood transfusion laboratories: do they go with the flow?. Issue 6 (18th August 2017) - Whitby, L.; White, J.; Fletcher, M.; Whitby, A.; Milkins, C.; Barnett, D.
SUMMARY: Paroxysmal nocturnal haemoglobinuria (PNH) is a rare stem cell disorder causing, in untreated patients, symptoms that include renal damage, thrombosis and increased mortality. When correctly diagnosed and treated, patients have reduced symptoms and normal life expectancies. Historically PNH testing resided within blood transfusion laboratories using techniques that were insensitive, for example, the Ham test. However, technology has evolved and flow cytometry is now regarded as the gold standard methodology. Given the clinical importance of diagnosing PNH correctly, we undertook a study to examine PNH testing procedures in blood transfusion laboratories within the UK and Ireland to determine implementation of best practices. An online survey was issued to 386 blood transfusion laboratories in the UK and Ireland requesting details of their current PNH testing practices and procedures. There were 143 responses, representing a 37% response rate. Of these, we identified seven laboratories undertaking PNH testing using obsolete methodologies. Furthermore, multiple centres did not refer samples for confirmatory testing by national PNH reference centres and inclusion on the national PNH disease registry. Staff handling requests for PNH testing should ensure that all samples are tested in accordance with current best practices using only flow cytometry.